كفاءة الخدمات الصحية في بلدية الدورة - الأسدي، علي لفتة سعيد Said, Ali Laftah; الهيتي، مازن عبدالرحمن جمعة (جامعة الكوفة - كلية الآداب, 2017)
من خلال دراسة وتحليل الواقع الصحي لبلدية الدورة وجد أن هناك تباين واضح في التوزيع المكاني للمؤسسات الصحية مقارنة بالحجم السكاني الأمر الذي انعكس على كفاءة الخدمات المقدمة وكفايتها ومن خلال المعايير التخطيطية المعتمدة من قبل وزارة الصحة العراقية تبين أن البلدية تخلو من المستشفيات والمراكز التخصصية بواقع (3) مستشفيات توزيع حسب حجم السكان الأمر الذي ينعكس على زيادة المساحة المخصصة للأغراض الصحية. كما هناك نقصا في أعداد المراكز الصحية طبقا للمعايير القياسية مما يعني وجود نقص وبواقع (29) مركزا صحيا. ولغرض رفع كفاءة هذه الخدمة لابد من إعادة النظر في التوزيع المكاني لهذه الخدمات ورفع مستوياتها من (مستشفيات ومراكز تخصصية) استجابة للنمو السكاني المتزايد وحاجة السكان الملحة لها.
Through the study and analysis of the health fact to the municipality dawra we found that there is difference in spatial distribution of health compared with numbers of population this is nega tively reflected at efficiency of the services given to the citizens and through the criteria planning and depend by the Iraqi Ministry of Health it becomes clear that the municipality with out of hospitals and dispensary which is specialized in this field in fact (3) hospitals distributed according to the quantity of population this is reflected at the increased one area which located for health purposes. also there is a shortage in the number of quantity of dispensaries according regular criteria that means there is a shortage about (29) dispensary approximately health centers. For the sack of increasing the efficiency of this service we should reconsidered spatial distribution of health services and raise the standared level of services in respect of (hospitals and health centers) this is due to increasing of population and the growing urgent need for its population.
Keywords: الخدمات الصحية -- المؤسسات الصحية -- بلدية الدورة -- مدينة بغداد -- العراق